Coco the essential guide - Dakin, Glenn (New York, New York DK Publishing, 2017)
Explore the art of the Disney movie Coco! Despite his family's baffling generations-old ban on music, Miguel dreams of becoming an accomplished musician like his idol, Ernesto de la Cruz. Desperate to prove his talent, Miguel finds himself in the stunning and colorful Land of the Dead following a mysterious chain of events. Along the way, he meets charming trickster Hector. Follow along with word-for-word narration as, together, they set off on an extraordinary journey to unlock the real story behind Miguel's family history
Based on an original screenplay by Adrian Molina
Comic strips
1 2
Keywords: Coco (Motion picture) -- Juvenile literature; Coco (Motion picture) -- Juvenile literature; All Souls' Day -- Mexico -- Art -- Juvenile literature; Animated films -- Juvenile literature; Motion pictures -- Art -- Juvenile literature; All Souls' Day -- Mexico -- Art -- Juvenile literature; Animated films -- Juvenile literature; Motion pictures -- Art -- Juvenile literature; Mexico -- Art -- Juvenile literature; Mexico -- Art -- Juvenile literature